PENGGUNAAN BEBERAPA HORMON ORGANIK SEBAGAI POC DALAM MEDIA TUMBUH UNTUK MENINGKATKAN PERTUMBUHAN Azolla Microphylla PAKAN TERNAK - Sembiring, Meriksa; Ginting, Risdawati br; Hia, Aro Setiawan; Putra, Andhika (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
The purpose of this study was to obtain a type of plant hormone that can increase growth and production Azolla mycrophyla to produce animal feed. Also to find out the hormones of certain types of plants that produce hormones for planting media Azolla mycrophylafor use as poultry feed. The materials used in this study are plants that have ZPT (hormones) and bioactivators. The experimental design used in this study was a non-factorial Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments tested were: taking hormones from: Zo (control) without hormones, Z1 (banana weevil), Z2 (bean sprouts), Z3 (sweet potato shoots). Hormone testing was taken from plants by adding EM4 bioactivator and molasses which was fermented for 2 weeks except for hormones from bean sprouts. The three results of fermentation are complete and can be used as a planting medium Azolla microphylla. Parameters observed are ready to be analyzed for growth in plant population numbers, colony diameter, production (g). The results of the measurement data obtained were tested using the DMRT program and continued with the Dun'can different test. From the research results that have been analyzed, it is found that the use of hormones derived from bean sprouts (C) shows a significant difference and is superior compared to the use of banana weevil and sweet potato shoots hormones, with growth and production (Z2 > Z1 > Z3) and the lowest with without the use of plant hormones (Zo). Keywords: Hormones, Azolla sp, fermentation, growth, production